2021
DOI: 10.1002/cncr.33529
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for progression in patients with Philadelphia chromosome‐positive acute lymphoblastic leukemia in complete molecular response within 3 months of therapy with tyrosine kinase inhibitors

Abstract: BACKGROUND The achievement of a 3‐month complete molecular response (CMR) is a major prognostic factor for survival in patients with Philadelphia chromosome (Ph)‐positive acute lymphoblastic leukemia (ALL). However, 25% of patients relapse during therapy with tyrosine kinase inhibitors (TKIs). METHODS The authors reviewed 204 patients with Ph‐positive ALL who were treated between January 2001 and December 2018 using the combination of hyper‐CVAD (hyperfractionated cyclophosphamide, vincristine, doxorubicin, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 26 publications
3
35
0
1
Order By: Relevance
“…Moreover, our study results supported the stronger efficacy of dasatinib and ponatinib than imatinib, in line with the result from a recent study [43]. However, the data on comparing the efficacy between each TKI are scarce, and more head-to-head studies are needed to investigate this issue.…”
Section: Plos Onesupporting
confidence: 90%
See 3 more Smart Citations
“…Moreover, our study results supported the stronger efficacy of dasatinib and ponatinib than imatinib, in line with the result from a recent study [43]. However, the data on comparing the efficacy between each TKI are scarce, and more head-to-head studies are needed to investigate this issue.…”
Section: Plos Onesupporting
confidence: 90%
“…of the status of transplantation. Results also suggested that negative minimal residual disease (MRD) status is also predictive of better survival outcomes and lower incidence of relapse compared to those with positive MRD in Ph + ALL, suggesting the potential of utilizing MRD status to classify patient subpopulation who would benefit from allo-HSCT [41][42][43]. Unfortunately, the data are still limited and more studies should explore further this subgroup of patients [11,14,16,34,37].…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations
“…When dasatinib was combined with intensive chemotherapy, the 3-year event-free survival and OS rates were 55% and 69%, respectively. In case of ponatinib a complete molecular response was increased to 74% in Ph+ ALL patients ( 13 ).…”
Section: Introductionmentioning
confidence: 99%